Transcendental Emancipatory Unification of Family Law in Muslim Majority Countries in Southeast Asia - Martha Eri Safira; Iffatin Nur; Abdul Mun’im Saleh; Uswatul Khasanah; Raihanah binti Abdullah (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
Transcendentally, the basis of legal reform in Muslim-majority Southeast Asian countries includes cultural and religious pluralism, social justice, modernity and tradition, globalization and interconnectivity, and politics and policy. Emancipatory family law reform is not only related to moral values. But it is also influenced by government policies, political dynamics, and the formation of laws that are responsive to the rights of children and women. The study aimed to analyze the politics of family law unification in Indonesia, Malaysia, and Brunei Darussalam and efforts to unify family law to protect women and children from an emancipatory transcendental perspective. The research method was normative empirical. Data analysis carried out inductively and structured from the politics of the formation and renewal of family law in Southeast Asia: Indonesia, Malaysia, and Brunei Darussalam. Through this research analysis, it concluded that political initiatives for family law reform are influenced by pressure from civil society, non-governmental organizations, human rights movements, and gender equality. Family law reform reflects power relations in society. Emancipatory transcendental analysis can deeply explore the structure of family law as a foundation for maintaining or changing policy direction, particularly regarding gender and individual rights under family law. This analysis creates the concept of emancipatory transcendental politics, which combines religious, customary, and Western law and creates gender equality and social justice in efforts to unify family law in Indonesia, Malaysia, and Brunei Darussalam.